Identification of key proteins and lncRNAs in hypertrophic cardiomyopathy by integrated network analysis - Xiaofeng Hu (Termedia Publishing House, 2019)
Introduction Hypertrophic cardiomyopathy (HCM), a genetically heterogeneous disorder of cardiac myocytes, is one of the main causes of sudden cardiac death of young people. However, the molecular mechanism involved in HCM has remained largely unclear. Of note, non-coding RNAs were reported to play an important role in human diseases. In this study, we focused on identifying differentially expressed long non-coding RNA (lncRNAs) and mRNAs in HCM by analyzing a public dataset (GSE36961).